Human-elephant interactions in the agriculture-forest interface : study of the Sebitoli area, north of Kibale National Park, Uganda - (:unkn) unknown (My University, 2021)
Human-wildlife conflict is widespread in Africa, and is expected to intensify due to the expansion of agriculture, and the reduction and fragmentation of habitat. Crop losses due to destruction by elephants create food insecurity, which increases poverty and hinders local support for conservation efforts. Elephants are often identified as the main responsible animals of crop losses. Using a multidisciplinary approach combining genetics, morphology, social sciences and eco-ethology, our study aims to (1) better characterize the actors and interactions at the edge of a protected area, where both species of elephants live, and where conflict is exacerbated by the proximity of human farming and elephant habitat; and (2) suggest effective, non-violent measures adapted to the local context. The perspectives are to submit recommendations for the management of human-wildlife conflict, in order to contribute to better protection of the fields, leading to the improvement of the living conditions of local communities, as well as the reduction of poaching pressure on the wildlife living in the park. We first showed that both African elephant species and hybrids are present in the Sebitoli area, in the North of the Kibale National Park, in Uganda. Studies of their behavior in the forest and during crop feeding episodes show that they live in mixed groups, and thus do not appear to exhibit crop feeding pattern that would be typical of forest or savannah elephants. Instead of adapting recommendations for crop protection measures according to elephant species, it seems essential that measures be adjusted to the geographical, land use, economic and social context of each village, considering the nocturnal behavior of elephants, as well as other species involved in human-wildlife conflict, including threatened and protected species such as chimpanzees.
Keywords: African Research